Why quantum engineering? - Zagoskin, A.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The progress in experimental techniques and theoretical modeling made possible to fabricate and test macroscopic structures, which use quantum coherent solid state qubits as building blocks. The results of such quantum engineering are likely to go far beyond the limited goals of quantum computing and quantum communication and provide a direct way to probing quantum-classical boundary. Some recent developments are discussed.